Preliminary Assessment of the Positional Accuracy of a Quickbird Ortho Image - Afonso, N. (2012)
This work has been accomplished on the scope of the GeoSAT research project, where the main goal was the definition of methodologies for geographic information extraction from high-resolution satellite images in an urban environment. This paper is intended to present and describe the positional quality assessment processes, of a QuickBird satellite ortho image from the city of Lisbon. For evaluate the possible applications of ortho images for information extraction and classification, for the Lisbon municipality base maps, it has been previously made some geometric pre-processing operations, using the 1/1000 municipality base map as a reference source. In order to obtain a significantly sample of independent ground control points, a set of GNSS (Global Navigation Satellite System(s)) observations have been made, in order to collect the ground coordinates and use them as reference information, having into consideration the specifications for the final product. The results obtained have shown that was not possible to reach the specifications for positional quality referring the 1/1000 scale, unlike smaller scales (for example, 1/5000). This way, the product could be used to perform other tasks more consistent with the results obtained and at same time, promote the update of Lisbon municipality base map.